Pengaruh Karakteristik Sedimen terhadap Distribusi dan Akumulasi Logam Berat Pb dan Zn di Perairan Sungai, Estuaria, dan Pantai - Najamuddin Najamuddin; Irmalita Tahir; Rustam E. Paembonan; Inayah Inayah (Universitas Diponegoro, 2020)
The purpose of the study was to analyze the effect of surface sediment characteristics including texture, organic carbon content, and redox potential of sediments on the distribution and accumulation of heavy metals Pb and Zn in three different water zones of each river, estuary and coast. Sediment texture was determined by pipette method, organic carbon content in sediments using Walkley and Black method, redox potential of sediments measured by Eh Meter, and concentrations of heavy metals Pb and Zn in sediments with Atomic Absorption Spectrophotometer with graphite furnace system. The results showed that the distribution and accumulation pattern of heavy metals Pb was similar to Zn where the highest concentration was in the coastal waters zone and the lowest was in the estuary waters zone. Sediment texture in the three zones of the dominant was sand. The percentage of organic carbon content in sediments ranges from 1.63-3.25% and the sediment redox potential was classified as reduction and transition zones. The parameters of texture, organic carbon content, and sediment redox potential have a significant influence on the distribution and accumulation of heavy metals Pb and Zn in sediments in all three water zones. Tujuan penelitian adalah menganalisis pengaruh karakteristik sedimen permukaan meliputi tekstur, kandungan karbon organik, dan potensial redoks sedimen terhadap distribusi dan akumulasi logam berat Pb dan Zn di tiga zona perairan berbeda masing-masing sungai, estuaria, dan pantai. Tekstur sedimen ditentukan dengan metode pipet, kandungan karbon organik dalam sedimen dengan metode Walkley and Black, potensial redoks sedimen diukur dengan Eh Meter, dan konsentrasi logam berat Pb dan Zn dalam sedimen dengan Spektrofotometer Serapan Atom dengan sistem graphite furnace. Hasil penelitian menunjukkan pola distribusi dan akumulasi logam berat Pb serupa dengan Zn dimana konsentrasi tertinggi di zona perairan pantai dan terendah zona perairan estuaria. Tekstur sedimen pada tiga zona perairan dominan berupa fraksi pasir (sand). Persentase kandungan karbon organik dalam sedimen berkisar antara 1,63-3,25 % dan nilai potensial redoks sedimen termasuk kategori zona reduksi dan transisi. Parameter tekstur, kandungan karbon organik, dan potensial redoks sedimen memberikan pengaruh nyata terhadap distribusi dan akumulasi logam berat Pb dan Zn dalam sedimen pada ketiga zona perairan.